2016
DOI: 10.3109/13685538.2016.1162783
|View full text |Cite
|
Sign up to set email alerts
|

Cross-sectional analysis between prostate volumes and serum sex hormones in Japanese men attending a urological clinic

Abstract: Serum T and E2 had significant positive correlation with measured PV especially in larger prostates. This result seems to correspond with the conventional theory that T and E2 have an etiological effect on benign prostatic hyperplasia. DHEAS did not show direct correlation with PV, however it appeared to suppress the role of T and E2 on benign prostatic hyperplasia growth. DHEAS might be a key to understanding the etiology of benign prostatic hyperplasia with aging.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 26 publications
0
3
0
Order By: Relevance
“…However, after adjusting for age, the results were not statistically significant 13 . In contrast, Nukui M et al 35 found that PV was positively correlated with TT, but this finding only existed in groups with PV > 25 ml in a cross-sectional study of 226 subjects. Other studies have also failed to find a significant association between TT level and PV 12 , 14 .…”
Section: Discussionmentioning
confidence: 81%
“…However, after adjusting for age, the results were not statistically significant 13 . In contrast, Nukui M et al 35 found that PV was positively correlated with TT, but this finding only existed in groups with PV > 25 ml in a cross-sectional study of 226 subjects. Other studies have also failed to find a significant association between TT level and PV 12 , 14 .…”
Section: Discussionmentioning
confidence: 81%
“…In present study, Tai Chi participants have significant higher ratio of DHEA to total testosterone not to free testosterone. However, the ratio of DHEAS to testosterone is reported negatively correlated to prostate volume (23). Moreover, Tai Chi training in patients with innocuous prostate hypertrophy is able to improve lower urinary tract symptoms as well as qual- Well-being encompasses not only the physical body but also the spiritual, mental and emotional parts of an individual's life.…”
Section: Discussionmentioning
confidence: 99%
“…The prostate gland (PG) is an exocrine gland tightly influenced by the endocrine milieu, as its development and homeostasis is regulated, for instance, by sexual hormones. Indeed, testosterone, the main sexual hormone responsible for prostate homeostasis, can be locally converted to dihydrotestosterone, which is involved in increasing proliferation and reducing death of PG cells . Moreover, a growing body of evidence indicates that the endocrine axis comprising growth hormone (GH), insulin and insulin‐like growth factor 1 (IGF1) is locally expressed in the PG and plays a relevant role in its pathophysiology .…”
Section: Introductionmentioning
confidence: 99%